Timing of stroke onset determines discharge‐functional status but not stroke severity: A hospital‐based study. Issue 1 (8th October 2012) - Liou, Li‐Min; Lin, Hsiu‐Fen; Tsai, Chin‐Ling; Lin, Ruey‐Tay; Lai, Chiou‐Lian
Abstract: Circadian variation of the onset time of acute ischemic stroke has been well studied. However, little is mentioned about the circadian variation of discharge‐stroke severity and discharge‐functional status. This study evaluated the impact of onset time on discharge‐stroke severity and the functional status of acute ischemic stroke. Brain magnetic resonance imaging was performed on 274 acute ischemic stroke patients (66.42% male; mean age = 64.81 ± 12.80 years). All times of onset were assigned to 4‐hourly periods (six groups) starting from midnight. Stroke severity/functional status was evaluated on admission and discharge using the National Institute of Health Stroke Scale (NIHSS) score/modified Rankin Scale (mRS) and Barthel Index (BI), respectively. Using mRS, but not NIHSS score and BI, it was possible to differentiate the best and worst groups on discharge. Patients in group 2 (4 to <8am ) and group 6 (8 to <12pm ) had best and worst functional status, respectively. To control other stroke risk factors, multiple logistic regression analyses were conducted to examine the role of onset time in discharge mRS. Aside from age, onset time was a significant indicator in mRS, while gender, hypertension, diabetes mellitus, hyperlipidemia, atrial fibrillation, and current smoking were not. In conclusion, there is also circadian variation of discharge‐functional status in patients with acute ischemic stroke when assessed by mRS.